Vanderbilt ebook The rise and fall of an american dynasty. - Cooper, Anderson (2021)
"Splendid. . . . haunting and beautifully written." — Washington Post The #1 New York Times bestselling chronicle of the rise and fall of a legendary American dynasty, from CNN anchor and journalist Anderson Cooper and historian and novelist Katherine Howe. One of the Washington Post's Notable Works of Nonfiction When eleven-year-old Cornelius Vanderbilt began to work on his father's small boat ferrying supplies in New York Harbor at the beginning of the nineteenth century, no one could have imagined that one day he would, through ruthlessness, cunning, and a pathological desire for money, build two empires—one in shipping and another in railroads—that would make him the richest man in America. His staggering fortune was fought over by his heirs after his death in 1877, sowing familial discord that would never fully heal. Though his son Billy doubled the money left by "the Commodore," subsequent generations competed to find new and ever more extraordinary ways of spending it. By 2018, when the last Vanderbilt was forced out of The Breakers—the seventy-room summer estate in Newport, Rhode Island, that Cornelius's grandson and namesake had built—the family would have been unrecognizable to the tycoon who started it all. Now, the Commodore's great-great-great-grandson Anderson Cooper, joins with historian Katherine Howe to explore the story of his legendary family and their outsized influence. Cooper and Howe breathe life into the ancestors who built the family's empire, basked in the Commodore's wealth, hosted lavish galas, and became synonymous with unfettered American capitalism and high society. Moving from the hardscrabble wharves of old Manhattan to the lavish drawing rooms of Gilded Age Fifth Avenue, from the ornate summer palaces of Newport to the courts of Europe, and all the way to modern-day New York, Cooper and Howe wryly recount the triumphs and tragedies of an American dynasty unlike any other. Written with a unique insider's viewpoint, this is a rollicking, quintessentially American history as remarkable as the family it so vividly captures.